ORAL CRYOTHERAPY MENCEGAH MUKOSITIS ORAL PADA PASIEN KANKER YANG MENJALANI KEMOTERAPI DI ODC RUMAH SAKIT SWASTA YOGYAKARTA - Neni Puspita Guningsih; Fransisca Anjar Rina Setyani; Elisabeth Herlina Suminarhati (Jurnal Keperawatan Malang, 2026)
Background: Cancer patients receiving chemotherapy agents often experience the side effect of oral mucositis. One complementary therapy to prevent oral mucositis is oral cryotherapy, as it causes vasoconstriction in the oral mucosa area, thereby reducing the amount of blood containing chemotherapy drugs reaching the oral mucosa area. Purpose: The objective of this study was to determine the effect of oral cryotherapy on reducing the severity of oral mucositis in cancer patients undergoing chemotherapy in the ODC chemotherapy room at Private Hospital in Yogyakarta Methods: This study used a quasi-experimental research design. The study population consisted of 38 cancer patients undergoing chemotherapy with doxorubicin, cyclophosphamide, and 5-fluorouracil. A sample of 32 respondents was selected using systematic sampling techniques and divided into two groups of 18 people each in the control and intervention groups. In the intervention group, respondents were instructed to brush their teeth, rinse their mouths, and then suck on ice chips over the entire surface of the oral mucosa for 20 minutes immediately after the chemotherapy drugs were administered and for 7 consecutive days thereafter, while the control group received no intervention. The author observed oral mucositis using the Oral Assessment Guide (OAG) on day 1 and day 7 Result: Data analysis using the Mann Whitney test showed that oral cryotherapy had an effect on the degree of oral mucositis in cancer patients undergoing chemotherapy in the ODC chemotherapy room at Private Hospital (P value = 0.00) Implication: Nurses can administer oral cryotherapy to prevent oral mucositis in cancer patients undergoing chemotherapy in the ODC Chemotherapy Room at Private Hospital in Yogyakarta Keywords: Cryotherapy; Mucositis; Chemotherapy